Síntese de catalisador organofuncionalizado a partir do rejeito de caulim - BRITO, Yrvana Pereira dos Santos (2019)
This work investigated the synthesis of catalysts functionalized with sulfonic groups, from the tailings generated from the kaolin processing step. In order that the reject could be used, it was first necessary to heat it in order to make it more susceptible to acid attack, and further to provide an acid leaching dealumination of the material to provide the waste the silica content as possible, making secondary functionality available with MTPS. The organic functional group anchored in the molecular sieve was then oxidized to its corresponding acid group, to form stronger acid sites. The heterogeneous catalyst was then tested in the esterification reaction of oleic acid with methanol at 130 ° C with ratio 1:30 (oleic acid / methanol) and at different times (30, 60, 90 and 120 minutes) and percentage of catalyst (1 %, 3% and 5%) relative to the mass of oleic acid. The conversion of the reaction was evaluated by titration with base and expressed as percentage of free fatty acids converted to methyl ester. And the best result was 96% conversion to the catalyst test, while that without catalyst test had only 19%. The catalyst was reused in the same reaction and the same conditions, since the reuse of a catalyst with good performance is one of the basic concepts of heterogeneous catalysis. And the result for the last reuse was 86%, proving the efficacy of this catalyst synthesized from -SO3H functionalized industrial kaolin waste.